Factors affecting the adoption of digital banking among Malaysians - Lee, Sean Qing Yang; Goh, Kai Hen; Loh, Meng Hao; Beh, Jocelyn Jia Xin (2024)
The majority of financial initiatives have moved from offline to online transactions and from manual to automated processes as a result of technological advancements. Digital banking is the transformation of all traditional banking services and operations into a digital environment, in which consumers do not have to visit physical branches in order to conduct any types of financial transaction. This study mainly focuses on the factors affecting the adoption of digital banking among adults in Malaysia. To be specific, the study will provide insights regarding whether convenience, perceived ease of use, perceived usefulness and facilitating conditions have a significant relationship on the behavioural intention to adopt digital banking among Malaysians. As such, the study has incorporated the theoretical frameworks: Extended Technology Model and Unified Theory of Acceptance and Use of Technology model, to further study the relationship between the independent variables and the dependent variable. Moreover, the primary research method used in this research was the survey questionnaire approach using Google Forms. With the use of non-probability sampling technique (convenience sampling), there was a total of 400 respondents, in which the data was then transferred to the Statistical Product and Service Solutions (SPSS) software to aid in our data analysis. To guarantee the calibre of the analysis results, the validity and reliability of the research items were examined. Some of the tests included in this research were Multicollinearity Testing, Normality Testing and Multiple Regression Analysis. Lastly, the research contains certain limitations and recommendations to improve the ideas for future scholars as well as the Malaysian Government to increase the awareness of digital banking and improve the digital financial literacy of individuals.